Secure Communication in Solar Panel Monitoring Systems Using SmartPLS - Ageng Setiani Rafika; Dhimas Tribuana; Rohim Rohim; Agung Rizky; Chua Toh Hua (Pandawan Sejahtera Indonesia, 2026)
This study investigates the factors shaping secure communication architecture in solar panel monitoring systems within smart grid environments, focusing on cybersecurity, data integrity, and system reliability. The integration of solar photovoltaic systems with digital monitoring networks enhances real-time energy management but introduces communication vulnerabilities affecting monitoring accuracy and operational stability. This study aims to assess how Network Security, Data Integrity, and System Reliability contribute to Secure Communication Architecture and Monitoring Performance. A quantitative research design was employed, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The research model included five constructs: Network Security, Data Integrity, System Reliability, Secure Communication Architecture, and Monitoring Performance. Results indicate that Network Security significantly and positively affects Secure Communication Architecture, while Data Integrity positively influences both Secure Communication Architecture and System Reliability. Furthermore, Secure Communication Architecture and System Reliability both contribute positively to Monitoring Performance. The measurement model demonstrated acceptable reliability and validity, confirming construct robustness. These findings highlight that effective solar panel monitoring systems depend not only on technical energy infrastructure but also on secure, reliable communication networks that ensure accurate and timely data exchange. The study concludes that strengthening cybersecurity mechanisms, data integrity controls, and communication reliability is essential to improve monitoring performance and support resilient smart grid-based renewable energy management.